A Synthetic Analog of Fibrinogen α27–50 Is an Inhibitor of Thrombin - Binnie, Cameron G; Lord, Susan T (Thrombosis and Haemostasis, 1991)
Binding of the synthetic peptide AAKDSDWPEASDEDWNYKAPSGAR, a fibrinogen α27–50 analog, to thrombin was studied by inhibition assays and affinity chromatography. Peptide α27–50 corresponds to a segment of human fibrinogen downstream from the thrombin cleavage site, with cysteine residues at positions 28, 36, 45 and 49 replaced by alanine. The peptide inhibited clotting of fibrinogen with an inhibition constant of 190–400 μM. Cleavage of fibrinopeptides A and B was inhibited by the peptide and the peptide was competitive with fibrinogen for thrombin. Inhibition of the small substrate tosyl-Gly-Pro-Arg-p-nitroaniline was not observed indicating that the peptide did not block the active site of the enzyme. Peptide α27–50 that was covalently linked to Sepharose bound active siteinhibited thrombin at low ionic strength and was eluted at higher salt concentration. The peptide was not cleaved on overnight exposure to thrombin as determined by reverse phase HPLC. In summary, the peptide bound to, but was not a substrate for thrombin. These results suggest that this region of fibrinogen contributes to binding of thrombin.